Challenges of teaching academic writing to ukrainian esl students - Kotys, Olena; Котис, Олена (Східноєвропейський національний університет ім. Лесі Українки, 2016)
Academic writing in English is one of the important tools that enable voices of Ukrainian scholars to be heard in the scientific world. Most of Ukrainian universities included this subject into their curricula. Students of the Foreign Philology Department at Lesia Ukrainka Eastern European National University study this subject during their MA course. Our article is based on the teaching experience gained in 2016. We singled out the most frequent challenges that Ukrainian instructors face when teaching academic writing to Ukrainian students. The main problems that occur are the following: students replicate the approaches they used at secondary school when wr iting compositions in case of writing academic essays, they sometimes fail to understand the purpose and type of an essay they are asked to write; inability to briefly and precisely describe visual information (charts, graphs and tables, etc.), inadequate use of synonyms and paraphrase, unsuccessful use of generalizations, making mistakes when writing summaries. Англомовне академічне письмо – одне з важливих інструментів спілкування українських науковців зі світовою науковою спільнотою. Більшість університетів України долучили цей предмет до навчальних планів. В інституті іноземної філології Східноєвропейського національного університету імені Лесі Українки «Академічне письмо» вивчають студенти-магістри. На основі досвіду викладання цього навчального курсу в 2016 році розглянуто основні труднощі, з якими стикаються українські викладачі. До першочергових проблем належать: калькування шкільних підходів при написанні академічних есе; нерозуміння типів есе та їх призначення; невміння коротко й предметно описувати візуальну інформацію (графіки, діаграми тощо); проблеми із застосуванням синонімів і перефразувань; невміле використання узагальнень при передачі інформації; помилки при написанні анотацій та рефератів.
«Виклики» при викладанні академічного письма англійською мовою для українських студентів
Keywords: academic style; English; writing; challenges; teaching methodology; Lesia Ukrainka Eastern European National University; Foreign Philology Department; paraphrase; generalization; synonyms; academic essays; академічний стиль; англійська мова; письмо; виклики; методика викладання; Східноєвропейський національний університет імені Лесі Українки; інститут іноземної філології; перефразування; узагальнення; синоніми; академічне есе